M & A in Vietnam: Trend and Legal Framework - Nguyen P. Phương; Indah Permata Sari (Fakultas Hukum, Universitas Warmadewa, 2019)
The trend of mergers and acquisitions (M&A) is overgrowing throughout the world, especially in Vietnam. Vietnam is one of the countries active in M&A activities. The development of M&A values in Vietnam from 2006 to 2017 and 2018 experienced a significant increase. The development of M&A in Vietnam shows a substantial increase from year to year. The total value of M&A in 2017 reached a record 10.2 billion, the highest level ever and rose 175% from 2016. In the first six months of 2018, the total value of M&A sales in Vietnam reached 3.55 billion (equivalent to 155% of the same period in 2017). So the trend of development of M&A in Vietnam is exciting to study. In addition to the development trends of M&A, another exciting thing to examine is the issue of a legal framework for M&A in Vietnam. There are three main legal aspects of M&A in Vietnam, first is Controlling Economic Concentration under the Law on Competition, Management of Investment Activities under the Law on Investment and Management of Companies ’Activities under the Corporate Law. Keywords: Legal framework; M&A